THE CULTURAL INDUSTRY AND THE ALIENATION OF THE MASSES: A COMPARATIVE ANALYSIS BETWEEN THE BOOM OF THE 20S AND THE CONTEMPORARY DIGITAL AGE - dos Santos, Aloísio Cassio; Aducci, Eduardo de Oliveira; Tolentino, Juliano Jose da Silva; Mazega, Marcio Gabriel Schinor; Rampim, Pedro Vinicius (Seven Editora, 2024)
The present study investigates the cultural legacies of the 1920s boom and its influence on the current cultural industry. The objective is to understand how the mechanisms of cultural production and consumption of that time shaped contemporary practices, perpetuating the alienation of the masses. Using a comparative approach, the study is based on a literature review and content analysis of primary and secondary sources, including works by Adorno and Horkheimer, as well as historical and contemporary data on cultural production. The methodology involves the detailed analysis of texts, films, music and other forms of media from the 20s, comparing them with the cultural productions of the digital age, such as social networks, streaming and other digital platforms. The results indicate that the cultural massification that began in the 1920s, driven by technological advances and the market economy, established the foundations for the modern cultural industry, characterized by globalization and digitalization. It is concluded that, despite technological changes, the principles of alienation and mass consumption remain central, evidencing the continuity and adaptation of cultural control strategies over time. This study contributes to a deeper understanding of the cultural and social dynamics that shape the perception and behavior of the masses in contemporary times, highlighting the historical relevance and persistence of cultural patterns established a century ago. In addition, the research underscores the importance of critically recognizing and analyzing these cultural heritages to better understand the challenges and opportunities present in the digital age. DOI:https://doi.org/10.56238/sevened2024.037-056